Beyond the commons: diagnosis and management of rare intra-abdominal masses-a case series - Nachiyar N., Indhumathi; C., Arunbabu; P., Dhanaraj; C., Varshini; Ranjeeth D., Gokul (International Surgery Journal, 2025)
Rare intra-abdominal masses pose significant challenges in diagnosis and management due to their uncommon presentation and varied etiology. This retrospective case series evaluates four unique cases, including primary retroperitoneal melanoma (PRM), small bowel leiomyosarcoma, ruptured desmoid tumor in familial adenomatous polyposis (FAP), and small intestinal Ewing’s sarcoma. Data were collected from the government Stanley medical college between 2019 and 2023. The study highlights the role of advanced imaging, immunohistochemistry, and multidisciplinary collaboration in improving diagnostic accuracy and treatment outcomes. Prognoses varied, with some cases showing poor outcomes despite aggressive management. This study underscores the necessity of individualized treatment protocols for such rare conditions.